Synthesis of self-templated urchin-like Ni2Co(CO3)2(OH)2 hollow microspheres for high-performance hybrid supercapacitor electrodes. (10th December 2019) - Liu, Lu; Yu, Haoming; Liu, Anru; Xu, Yuhan; Feng, Bo; Yang, Fangqi; Zhang, Peixin; Wang, Jun; Deng, Qiang; Zeng, Zheling; Deng, Shuguang
Abstract: Developing novel nanostructures is always the most decisive aspect for high-performance supercapacitor electrodes. Thus, a facile one-step and self-templated method is successfully developed for the fabrication of urchin-like Ni2 Co(CO3 )2 (OH)2 hollow microspheres (NiCoHSs) as a high-performance hybrid supercapacitor electrodes. The synthesis conditions are carefully adjusted and the mechanisms of morphology transformation are clearly illustrated. The favorable morphology with a large specific surface area, suitable pore sizes, and good conductivity endows a high specific capacity (890.8 C g −1  at 0.5 A g −1 ) and excellent rate retention (700.8 C g −1  at 50 A g −1 ), and high stability (87.5% over 5000 cycles), which outperforms most reported electrodes based on nickel-cobalt oxides/hydroxides. Contributed by the uniquely engineered electrodes, a high-performance hybrid supercapacitor (HCS) is assembled, which exhibited a high specific capacity of 256.9 C g −1 (160.5 F g −1 ) at 0.5 A g −1 with an operating voltage of 1.6 V and an outstanding energy density of 57.1 W h kg −1  at a power density of 400.0 W kg −1 . This work offers a facile self-templated method to fabricate bimetal Transition-metal oxides (TMOs) electrodes for hybrid supercapacitors.